Substance Use Among Residents of Homeless Shelters During the COVID-19 Pandemic: Findings From France - Honor Scarlett; Maria Melchior; Maria Melchior; Camille Davisse-Paturet; Tarik El. Aarbaoui; Cécile Longchamps; Natasha Figueiredo; Simon Ducarroz; Simon Ducarroz (Frontiers Media S.A., 2022)
Objectives: To record the prevalence and risk factors of substance use amongst homeless persons during the COVID-19 pandemic.Methods: The ECHO study consisted in two independent cross-sectional waves of data collection in the regions of Paris, Lyon, and Strasbourg during the Spring of 2020 (n = 530) and 2021 (n = 319). Factors associated with substance use were explored using generalised logistic regression models.Results: The most prevalent substance used was tobacco (38%-43%), followed by alcohol (26%-34%). The use of both substances positively associated with each other, although risk factors varied depending on the substance. The only factors consistently associated with alcohol and tobacco use were being male, exposure to theft/assault and participants' region of origin. Whilst the rate of tobacco use was relatively stable between Spring 2020 and 2021, alcohol use was more common in 2021.Conclusion: These findings highlight a high prevalence of substance use amongst homeless persons. People experiencing homelessness face specific challenges in the context of the pandemic, alongside greater vulnerability to illness and low healthcare access, therefore the need to improve prevention and support services for substance abuse within this population is vital.